KRITIK IBNU KHALDUN TERHADAP METODE MENGHAFAL TANPA PEMAHAMAN DALAM PENDIDIKAN ISLAM - Syahiratuszahra Annur Fadiah; Fina Safira; Naila Cahaya Fitri; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
This article examines Ibn Khaldun's critique of rote memorization without comprehension in Islamic education and its relevance to modern educational practices. Using a library research approach with content analysis technique, this study explores Ibn Khaldun's thought as articulated in the Muqaddimah and other relevant sources. The findings indicate that Ibn Khaldun viewed education as a process of developing intellect and character, not merely accumulating memorized content. He sharply criticized mechanical teaching methods for weakening students' reasoning capacities. This research finds that such criticism remains highly relevant in addressing the modern educational phenomenon of examination-oriented and rote-memorization-based learning. Ibn Khaldun offers a graduated, comprehension-based, and humanistic learning model suited to the intellectual development of students. By integrating this thought into contemporary Islamic educational curricula, it is hoped that a generation of Muslims will emerge who not only memorize religious texts but also understand, internalize, and apply their values critically and creatively.